Qualitative investigation of the factors that generate ambivalent feelings in women who give birth after receiving negative results from non-invasive prenatal testing - Junko Yotsumoto (BMC Pregnancy and Childbirth, 2020)
Abstract Background Women who receive negative results from non-invasive prenatal genetic testing (NIPT) may find that they later have mixed or ambivalent feelings, for example, feelings of accepting NIPT and regretting undergoing the test. This study aimed to investigate the factors generating ambivalent feelings among women who gave birth after having received negative results from NIPT. Methods A questionnaire was sent to women who received a negative NIPT result, and a contents analysis was conducted focusing on ambivalent expressions for those 1562 women who responded the questionnaire. The qualitative data gathered from the questionnaire were analyzed using the N-Vivo software package. Results Environmental factors, genetic counseling-related factors, and increased anticipatory anxiety, affected the feeling of ambivalence among pregnant women. Furthermore, pregnant women desired more information regarding the detailed prognosis for individuals with Down syndrome and living with them and/or termination, assuming the possibility that they were positive. Conclusions Three major interrelated factors affected the feeling of ambivalence in women. Highlighting and discussing such factors during genetic counseling may resolve some of these ambivalences, thereby enhancing the quality of decisions made by pregnant women.